Status, Magic and Belief: Exploring Identity through Dress Accessories and Other Amulets in Medieval Scotland: A Perthshire Case-study. Issue 3 (December 2021) - Hall, Mark A.
Abstract : This paper explores belief and identity as expressed through the material culture of dress. It focuses on supernatural engagements through material culture linked to human and animal bodies and offers a view of the means by which everyday ritual, habit and devotion were embodied and facilitated through dress and other amulets, including contextually re-purposed coins. The evidence is primarily archaeological and derives from medieval Perthshire, a place with wide connections, and so the discussion is presented in the context of Scottish and European practices. The key themes are status, magic and belief, all three of which speak to identity. The practices they elucidate are explored primarily through jewellery and dress fittings, pilgrimage souvenirs, coins and other amulets.